2020
DOI: 10.13057/biodiv/d210410
|View full text |Cite
|
Sign up to set email alerts
|

Management practices and contribution of village chickens to livelihoods of communal farmers: The case of Centane and Mount Frere in Eastern Cape, South Africa

Abstract: Abstract. Gunya B, Muchenje V, Gxasheka M, Tyasi LT, Masika PJ. 2020. Management practices and contribution of village chickens to livelihoods of communal farmers: The case of Centane and Mount Frere in Eastern Cape, South Africa. Biodiversitas 21: 1345-1351. This study was conducted to determine village chickens production practices and their contribution to the livelihoods of farmers in rural households of the Eastern Cape Province, South Africa. Data were gathered using a questionnaire survey of 150 househo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
(23 reference statements)
1
9
0
Order By: Relevance
“…According to Table 2, many of the farmers (44.6%) are known for rearing village chickens as a source of income, while a few (28.3%) were engaged in rearing both hybrid and village chickens and nearly half (43.5%) of the farmers had less than 50 birds size. This agreed with a study by Gunya [30] which indicated the important contribution of local chickens towards income generation for farmers.…”
Section: Farmer's Poultry Production and Operation Capacitysupporting
confidence: 92%
“…According to Table 2, many of the farmers (44.6%) are known for rearing village chickens as a source of income, while a few (28.3%) were engaged in rearing both hybrid and village chickens and nearly half (43.5%) of the farmers had less than 50 birds size. This agreed with a study by Gunya [30] which indicated the important contribution of local chickens towards income generation for farmers.…”
Section: Farmer's Poultry Production and Operation Capacitysupporting
confidence: 92%
“…They provide livelihood security to the family in addition to securing the availability of food reducing the poverty. Unemployed youth and women can also earn an income through poultry farming by selling chickens (Gunya et al, 2020). They grow slowly and take time to reach maturity due to their behaviour since are scavenging and poor productivity under an extensive farming system .…”
Section: Advances Inmentioning
confidence: 99%
“…The advantage in this regard is that these chickens are mostly reared with limited outlay, which makes them affordable for almost every household. A study by Gunya et al [59] reported on the contribution of local chickens towards income generation for local farmers. In South Africa, an average of R80 (USD 7.22) per chicken has been found to be the amount a farmer can generate from the sale of chickens [59].…”
Section: Importance Of Local Chickens In Alleviating Household Povertymentioning
confidence: 99%
“…A study by Gunya et al [59] reported on the contribution of local chickens towards income generation for local farmers. In South Africa, an average of R80 (USD 7.22) per chicken has been found to be the amount a farmer can generate from the sale of chickens [59]. However, it is evident that the low production rate among local chickens negatively affects the decision of whether to sell or to consume.…”
Section: Importance Of Local Chickens In Alleviating Household Povertymentioning
confidence: 99%